Homosexuality in Renaissance and Enlightenment England : literary representations in historical context - Summers, Claude (London: Harrington Park Press, 1992)
"Claude Summers Fonds Suzan Daniel (FSD) ook uitgegeven als Journal of Homosexuality 23(1992) 1-2"